1971
DOI: 10.1098/rstb.1971.0102
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the caudate nucleus of the cat: light and electron microscopy

Abstract: The caudate nucleus of the cat appears to be homogeneous when examined with the light or electron microscope, except for a layer beneath the ependyma where there is a high concentration of glial cells and few neurons. In sections of brains stained with thionin the nerve cells in the caudate nucleus fall into three size groups: less than 8 μm, 9 to 18 μm, greater than 20 μm. Examination of material impregnated with the Golgi technique shows that there are six cell types (one small, four medium and one large), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 622 publications
(147 citation statements)
references
References 26 publications
7
139
1
Order By: Relevance
“…In light of these issues, we next estimated the positive predictive value of correctly assigning a nonfluorescent cell in a single transgenic line to the opposite pathway by evaluating the percentage of striatal neurons that fail to be identified by either pathway marker. Because MSNs comprise Ͼ90% of the total striatal neurons (Kemp and Powell, 1971;Gerfen, 2004), these numbers provide a close approximation of the number of unlabeled MSNs.…”
Section: Resultsmentioning
confidence: 99%
“…In light of these issues, we next estimated the positive predictive value of correctly assigning a nonfluorescent cell in a single transgenic line to the opposite pathway by evaluating the percentage of striatal neurons that fail to be identified by either pathway marker. Because MSNs comprise Ͼ90% of the total striatal neurons (Kemp and Powell, 1971;Gerfen, 2004), these numbers provide a close approximation of the number of unlabeled MSNs.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the medium spiny cells of the neostriatum were thought to be local circuit neurons because of their locally arborizing axons (Fox et al, 1971;Kemp and Powell, 1971), but recent studies exploiting the intracellular injection of HRP have revealed that these neurons do have local axonal branches within the neostriatum, but they also have axonal branches to the globus pallidus and substantia nigra (Preston et al, 1980). Closer to the subject of our study is the Golgi analysis of the ventral posterior nucleus showing cells that have local axonal branches (Tbmbol, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…It is the target of inputs from the entire cortex and certain thalamic nuclei (parafascicular and centromedian nucleus) and provides output to other nuclei of the basal ganglia. The striatum is composed primarily of spiny projection neurons (DiFiglia et al, 1976;Bishop et al, 1982;Gerfen and Wilson, 1996), which constitute ϳ95% of the striatal neuronal population (Kemp and Powell, 1971). These projection neurons are also the major target of afferents to the striatum.…”
Section: Abstract: Striatum; Dopaminergic Cells; Parkinson's Diseasementioning
confidence: 99%